Compounding in Namagowab and English: (exploring meaning creation in compounds) - Caroline, Kloppert (Linguistics, 2016)
This essay investigates compounding in Namagowab and English, which belong to two widely divergent groups of languages, the Khoesan and Indo-European, respectively. The first motive is to investigate how and why new words are created from existing ones. The reading and data interpretation seeks an understanding of word formation and an overview of semantic compositionality, structure and productivity, within the broad context of cognitive, lexicalist and distributed morphology paradigms. This coupled with history reading about the languages and its people, is used to speculate about why compounds feature in lexical creation. Compounding is prevalent in both languages and their distance in terms of phylogenetic relationships should allow limited generalizing about these processes of formation. Word lists taken from dictionaries in both languages were analyzed by entering the words in Excel spreadsheets so that various attributes of these words, such as word type, compound class (Noun, Verb, Preposition, Adjective and Adverb) and constituent class could be counted, and described with formulae, and compound and constituent meaning analyzed. The conclusion was that socio historical factors such as language contact, and aspects of cognition such as memory and transparency, account for compounding in a language in addition to typology.